Dual Role of Gibberellin in Perennial Shoot Branching: Inhibition and Activation - Katyayini, Niveditha Umesh; Rinne, Päivi L. H.; Tarkowská, Danuše; Strnad, Miroslav; van der Schoot, Christiaan (Frontiers in Plant Science, 2020)
Shoot branching from axillary buds (AXBs) is regulated by a network of inhibitory and promotive forces, which includes hormones. In perennials, the dwarfed stature of the embryonic shoot inside AXBs is indicative of gibberellin (GA) deficiency, suggesting that AXB activation and outgrowth require GA. Nonetheless, the role of GA in branching has remained obscure. We here carried out comprehensive GA transcript and metabolite analyses in hybrid aspen, a perennial branching model. The results indicate that GA has an inhibitory as well as promotive role in branching. The latter is executed in two phases. While the expression level of GA2ox is high in quiescent AXBs, decapitation rapidly downregulated it, implying increased GA signaling. In the second phase, GA3ox2-mediated de novo GA-biosynthesis is initiated between 12-24 h, prior to AXB elongation. Metabolite analyzes showed that GA1/4 levels were typically high in proliferating apices and low in the developmentally inactive, quiescent AXBs, whereas the reverse was true for GA3/6. To investigate if AXBs are differently affected by GA3, GA4 and GR24, an analog of the branch-inhibitor hormone strigolactone, they were fed into AXBs of single-node cuttings. GA3 and GA4 had similar effects on GA and SL pathway genes, but crucially GA3 induced AXB abscission whereas GA4 promoted outgrowth. Both GA3 and GA4 strongly upregulated GA2ox genes, which deactivate GA1/4 but not GA3/6. Thus, the observed production of GA3/6 in quiescent AXBs targets GA1/4 for GA2ox-mediated deactivation. AXB quiescence can therefore be maintained by GA3/6, in combination with strigolactone. Our discovery of the distinct tasks of GA3 and GA4 in AXB activation might explain why the role of GA in branching has been difficult to decipher. Together, the results support a novel paradigm in which GA3/6 maintains high levels of GA2ox expression and low levels of GA4 in quiescent AXBs, whereas activation and outgrowth require increased GA1/4 signaling through the rapid reduction of GA deactivation and subsequent GA biosynthesis.